Efikasi diri dan job crafting pada karyawan perhotelan: Menguji peran person job-fit sebagai moderator: Self-efficacy and job crafting in the hospitality sector: The moderating role of person job-fit - Maharani Tyas Budi Hapsari (Persona:Jurnal Psikologi Indonesia, 2025)
Global business dynamics demand employees to be proactive and adaptive, but not all individuals are able to adapt optimally. This condition emphasizes the importance of psychological factors and individual-job fit in encouraging adaptive behavior. This study aims to examine the relationship between self-efficacy and job crafting through person-job fit as a moderator. The study participants were 205 hospitality sector workers obtained through purposive sampling technique. This study used three scale instruments: the job crafting scale (α = 0.894), the occupational self-efficacy scale (α = 0.945), and the person-job fit scale (α = 0.889). The research data were analyzed using a moderation test with the help of the Hayes Process program. The findings of this study confirm that self-efficacy is the main psychological factor that directly encourages job crafting. Person-job fit does not significantly moderate the relationship between self-efficacy and job crafting. Hospitality organizations need to prioritize strengthening employee self-confidence through training, coaching, and mentoring to improve proactive work behavior. Keywords: Hospitality Employees; Job crafting; Person-Job Fit; Self-efficacy